Immobilization of α-Chymotrypsin on the Surface of Magnetic/Gold Core/Shell Nanoparticles - Mahmoud Kamal Ahmadi; Manouchehr Vossoughi (Journal of Nanotechnology)
Over the last decade, nanoparticles used as protein carriers have opened new avenues for a variety of biomedical applications. The main concern for these applications is changes in biological activity of immobilized proteins due to conformational changes on the surface of the carrier. To evaluate this concern, the preparation and biocatalyst activity of α-chymotrypsin-Fe3O4 @ Au core/shell nanoparticles were investigated. First, Fe3O4 @ Au core/shell nanoparticles were synthesized by coprecipitation method and citrate reduction of HAuCl4. TEM imaging revealed a core size of 13 ± 3 nm and a shell thickness of 4 ± 1 nm for synthesized nanoparticles. X-ray diffraction (XRD) was used to study the crystalline structure of the nanoparticles. Next, the enzyme was immobilized on the surface of synthesized nanoparticles by covalent bonding of Au shell with thiol and amine groups present in the protein structure (e.g., cysteine and histidine residues). FTIR and fluorescence spectroscopy were utilized to study secondary and tertiary structures of the immobilized enzyme. Results show that the secondary and tertiary structures of the enzyme remain virtually unchanged after immobilization on the nanoparticles surface. However, the biocatalyst activity of the enzyme was reduced by thirty percent, indicating possible conformational changes or active site occlusion.